2007
DOI: 10.1093/ajcn/85.5.1375
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with iron and riboflavin enhances dark adaptation response to vitamin A–fortified rice in iron-deficient, pregnant, nightblind Nepali women

Abstract: Background: Nightblindness affects 16 -52% of pregnant women in areas of Nepal and in some cases persists after vitamin A treatment. Iron and riboflavin affect vitamin A utilization and photoreceptor function, respectively, and pilot data in the study population showed a high prevalence of iron and riboflavin deficiencies. Objective: The objective was to assess the effect of supplemental iron and riboflavin on pupillary threshold (PT) and plasma retinol in nightblind, pregnant Nepali women given vitamin A-fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Reported prevalences include 77% in lactating urban Guatemalan women (LH Allen and MT Ruel, unpublished data), 85% in night-blind pregnant Nepali women (21), 14% in Ghanaian infants (4), 30% in Kenyan school children (22), and in 1982, nearly all pregnant and lactating women and their infants in The Gambia (23). Recently, it was reported that 66% of adults in the UK, if they are low milkconsumers, have marginal riboflavin status correctable by supplementation (24).…”
Section: Riboflavinmentioning
confidence: 99%
“…Reported prevalences include 77% in lactating urban Guatemalan women (LH Allen and MT Ruel, unpublished data), 85% in night-blind pregnant Nepali women (21), 14% in Ghanaian infants (4), 30% in Kenyan school children (22), and in 1982, nearly all pregnant and lactating women and their infants in The Gambia (23). Recently, it was reported that 66% of adults in the UK, if they are low milkconsumers, have marginal riboflavin status correctable by supplementation (24).…”
Section: Riboflavinmentioning
confidence: 99%
“…There are scarce reports on PLP and riboflavin in infants, but studies from both highincome and low-income countries have reported a rather high deficiency incidence of both vitamins among pregnant and lactating women (99,107,271), something which may have serious implication for their breastfed infants.…”
Section: Determinants Of B Vitamin Status In Infantsmentioning
confidence: 99%
“…Specifically, studies in pregnant women have shown greater improvements in the relative dose-response test and in dark adaptation when VA was coadministered with iron or iron plus riboflavin, compared with VA supplementation alone. 79,80 Reduced plasma retinol concentrations have been observed in anemic rats, 81 even when animals were fed a VA-rich diet, 82 and are associated with VA accumulation in the liver and a higher molar ratio of liver retinyl esters/retinol. 82,83 These relationships have also been investigated by model-based compartmental analysis, which showed decreased absorption of VA and inhibited mobilization of VA stores in diet-induced iron deficiency in rats.…”
Section: Current Limitations Of the Isotope Dilution Techniquementioning
confidence: 99%